2020
DOI: 10.21203/rs.3.rs-28130/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Candidate multi-epitope vaccine against SARS-CoV-2

Abstract: In the past two decades, 7 coronaviruses have infected the human population, with two major outbreaks caused by SARS-CoV and MERS-CoV in the year 2002 and 2012, respectively. Currently, the entire world is facing a pandemic of another coronavirus, SARS-CoV-2, with a high fatality rate. The spike glycoprotein of SARS-CoV-2 mediates entry of virus into the host cell and is one of the most important antigenic determinants, making it a potential candidate for a vaccine. In this study, we have computationally desig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 84 publications
1
11
0
Order By: Relevance
“…Further to ensure the higher expression of the designed vaccine construct in prokaryote host, codon optimization and in silico cloning were performed. The CAI (0.97) and GC content (53.73%) were promising and within the acceptable range for high level expression of protein E. coli K12 (Kar et al 2020). Further, the immune simulation study of the designed vaccine construct revealed promising outcomes in terms of both humoral and cellular immune response.…”
Section: Discussionmentioning
confidence: 88%
“…Further to ensure the higher expression of the designed vaccine construct in prokaryote host, codon optimization and in silico cloning were performed. The CAI (0.97) and GC content (53.73%) were promising and within the acceptable range for high level expression of protein E. coli K12 (Kar et al 2020). Further, the immune simulation study of the designed vaccine construct revealed promising outcomes in terms of both humoral and cellular immune response.…”
Section: Discussionmentioning
confidence: 88%
“…Over the last few months, there have been various studies on the identification of immunogenic epitopes from SARS-CoV-2 using computational techniques. But, these studies focus on a particular viral protein [24][25][26] , identifying epitopes from SARS-CoV which shows high sequence similarity along with sequence conservation to SARS-CoV-2 27 or considering viral sequences from diverse geographical regions 28 . Unlike the other studies, our analysis primarily targets the Indian population where an infectious disease could escalate very rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…In silico methods for vaccine development could be the alternative methods to conventional methods which are complex and time-consuming. Many bioinformatics-based approaches are used to design novel drugs [ 52 , 53 ] and vaccines [ 54 , 55 ] to curb this disease. In silico methods are effective, safe, and less time-consuming.…”
Section: Discussionmentioning
confidence: 99%